Responsibility of Regional Notary Supervisory Council for Protocol Transfer of Died Notary - Gunawan Wibisono; Ngadino Ngadino (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The purpose of this study was to analyze: 1) The role of the Regional Supervisory Council on the responsibility of the Notary Public Protocol who has passed away in Jepara Regency. 2). The liability of the heirs to the protocol of the deceased notary public. The approach method to discuss this research is juridical empirical. This type of research is classified as a descriptive analytical research. Data collection was obtained from primary data and secondary data, by means of interviews and literature study. The data analysis technique is qualitative data analysis. The research results are: 1). The role of the Regional Supervisory Council for the responsibility of the Notary Public Protocol who has passed away in Jepara Regency, namely the MPD of the Jepara Regency working area as the supervisory council has played an active role in providing guidance and supervision to Notaries. MPD's firmness, especially regarding the Notary protocol that must be applied, so that when a Notary dies, such as the case of notary Muhammad Chaidzar, SH. M.Kn, and the protocol has been submitted to another notary appointed by the MPD. Legal aspects related to the accountability of the heirs of a capable Notary by immediately submitting the Notary protocol to another Notary who is appointed by MPD as the Notary holding the protocol. 2). The obligation of the heirs to the protocol of the deceased Notary is that the State archives in the form of documents that have been made by the notary must be kept, by submitting the Notary protocol through the MPD because of its authority. The responsibility of a notary public for a notary protocol that has not been submitted to another notary in this case can be categorized as an act of legal competence. Actions proficient in law here are defined as the implementation of the heir's responsibility in carrying out or submitting the protocol of the deceased.